Epidemiology of dengue fever in India, based on laboratory surveillance data, 2014–2017. (July 2019) - Murhekar, Manoj; Joshua, Vasna; Kanagasabai, K.; Shete, Vishal; Ravi, M.; Ramachandran, R.; Sabarinathan, R.; Kirubakaran, B.; Gupta, Nivedita; Mehendale, Sanjay
Highlights: DHR/ICMR has established a network of Virus Research and Diagnostic Laboratories to strengthen the laboratory capacity in the country. The laboratory surveillance data from 52 VRDLs indicate that more than one-fourth of the acute febrile illness patients were due to dengue. Dengue was the second commonest etiology of suspected outbreaks diagnosed by the network of virology laboratories established by ICMR/DHR. This laboratory network also provides a unique opportunity to generate additional data on dengue epidemiology. Abstract: Objectives: The Indian Council of Medical Research and the Department of Health Research have established a network of Virus Research and Diagnostic Laboratories (VRDL) to strengthen laboratory capacity in India. We analyzed the data generated by the 52 VRDLs during 2014–2017 to describe the epidemiology of dengue fever (DF) in India. Methods: As per the laboratory protocol, suspected DF patients reporting to various hospitals where VRDLs are located, or samples from suspected DF outbreaks are investigated for the presence of NS1 antigen or IgM antibodies against dengue. The data were analyzed to describe the distribution of DF by time (month and year), place (district and state) and person (age and sex) characteristics. Results: Between 2014–2017, VRDLs investigated 211, 432 suspected DF patients, 28.4% of whom were serologically confirmed. The median age of dengue positive patients was 25 years (IQR: 16-36). Dengue positivity was significantly higher among males. The mean monthly dengue positivity ranged from 7.7% to 37%, with higher positivity reported during September and October months. VRDLs provided diagnosis to 190 suspected outbreaks. Conclusions: The data from the VRDL network indicate dengue was the etiology in one-fourth of AFI cases. Dengue was the second commonest etiology of suspected outbreaks diagnosed by VRDLs.